Integration of Learning Beyond the Classroom and Project-Based Learning in a Nature-Based Elementary School - Januardi, Ega; Cholily, Yus Mochamad; Syaifuddin, Mohammad (Mimbar Sekolah Dasar, 2025)
This study is motivated by the limited effectiveness of conventional teaching methods that continue to dominate elementary education practices, particularly in fostering students’ conceptual understanding and 21st-century skills. The main objective is to explore the integration of Learning Beyond the Classroom (LBC) and Project-Based Learning (PjBL) as innovative strategies to improve learning quality. Employing a qualitative approach with a case study design, the research involved four teachers and twelve students from a Nature-Based Elementary School selected purposively. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman model. Validation was ensured through source triangulation and member checking. The findings indicate that the integration of LBC and PjBL significantly enhanced students’ critical thinking, collaboration, and conceptual understanding. Students also demonstrated improvements in metacognitive awareness, learning independence, and socio-emotional skills. Learning became more meaningful as activities were connected to real-life experiences, increasing student engagement and motivation. However, challenges emerged, including limited facilities, varying levels of teacher readiness, and technical constraints in online learning integration. Overall, the approach proved effective in enhancing the quality of elementary education. The implications emphasize the importance of teacher professional development, flexible and context-responsive curricula, and adequate infrastructure to support the sustainable implementation of contextual and experiential learning.